Occupational Health and Safety in Latin America: Diseases and Public Spending (Revista ABRA, 2021)
Social protection includes decent work, this being the main way out of the poverty of individuals and communities in Latin American countries. As health and social security services in different countries of Latin America include percentage of the population with multiple benefits in social protection. In the present study, he evidenced that there are more people affected with some exceptions, due to the lack of universal access to quality health and others that do not have universal health coverage, mostly because they live in conditions of greater vulnerability. An exploratory-qualitative study were applied, with technological watch techniques. Data base of the Health Information Platform in the Americas (Health Information Platform for the Americas, PLISA), and mortality indicators of communicable and non communicable diseases, cardiovascular diseases in six Latin American countries were analyzed, as well as aspects of social policy in public spending as percentages of GDP. There was an improvement on general health of population in countries such as Chile with greater percentage social protection coverage in Chile, Argentina and Brazil. However, there are a high mortality on non-communicable diseases (NCDs) such as cardiovascular diseases in countries such as Colombia and Venezuela. The highest public expenditure on health as percentage of GDP is Costa Rica, Argentina and Chile.